The effect of Avoparcin on the performance of grazing steers - Corah, L.R.; Busby, W.D.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
One hundred two steers were used to study the effect of Avoparcin on the performance of grazing steers. Four desired dosages -- 0. 200, 400. and 600 mg/head/day -- were compared in a self-fed mineral mix. Feeding Avoparcin at the desired level of 400 mg/head/day increased steer gains By 22%.
Keywords: Beef; Performance; Steers